PENGARUH EMPLOYER BRANDING DAN KOMPENSASI TERHADAP EMPLOYEE ENGAGEMENT PADA KARYAWAN BPR DAERAH GUNUNG SARI - Asri, Ni Wayan Adelia Mutiara; Hasany, Tifani Dame; Cahyaningrum, Dinis; Safitri, Dhanny; Ibrahim, Isra Dewi Kuntary (Bisnis-Net, 2025)
The urgency to retain high-quality human resources requires companies to continuously develop strategies that can enhance employee engagement with the organization. Employee engagement is a key indicator reflecting the extent to which employees feel emotionally and professionally connected to their workplace. Two factors considered influential in shaping this engagement are employer branding and compensation. This study aims to examine the influence of employer branding and compensation on employee engagement among employees of BPR in Gunung Sari. A quantitative approach was employed, involving a population of 30 BPR employees located in the Gunung Sari area. Data analysis was conducted using multiple linear regression. The findings indicate that employer branding has a positive and significant effect on employee engagement among BPR employees in Gunung Sari. Furthermore, compensation was also found to have a positive and significant influence on the level of employee engagement within the same organization.